Boundary triples for integral systems - Strelnikov, D.I. (Reports of the National Academy of Sciences of Ukraine, 2018)
An integral system that contains the Sturm—Liouville equation, Stieltjes string, and Krein—Feller string as special cases is considered. The maximal and minimal linear relations associated with the system are studied in a connected Hilbert space. Boundary triples and corresponding Weyl functions for the maximal linear relation are constructed in both limit circle and limit point cases.